2014
DOI: 10.2478/arsa-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Positional Accuracy Assessment of Googleearth in Riyadh

Abstract: Google Earth is a virtual globe, map and geographical information program that is controlled by Google corporation. It maps the Earth by the superimposition of images obtained from satellite imagery, aerial photography and GIS 3D globe. With millions of users all around the globe, GoogleEarth® has become the ultimate source of spatial data and information for private and public decision-support systems besides many types and forms of social interactions. Many users mostly in developing countries are also using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…While the horizontal accuracy of Google Earth images has not been conducted systematically across the world, studies indicate an average value of 2.18 meters for root-mean-square error (Farah and Algarni 2014 We also find biases in Google relative to GPS measures in the Viet Nam input demand estimates. Google estimates bias in the intensive margin of organic fertilizer demand downward by 32.4 percentage points and in the extensive margin of hired labor demand by 11.5 percentage points (Table 8).…”
mentioning
confidence: 67%
“…While the horizontal accuracy of Google Earth images has not been conducted systematically across the world, studies indicate an average value of 2.18 meters for root-mean-square error (Farah and Algarni 2014 We also find biases in Google relative to GPS measures in the Viet Nam input demand estimates. Google estimates bias in the intensive margin of organic fertilizer demand downward by 32.4 percentage points and in the extensive margin of hired labor demand by 11.5 percentage points (Table 8).…”
mentioning
confidence: 67%
“…Thus, the exterior orientation will absorb some interior errors, thereby influencing the orientation accuracy of the whole image. Many studies have shown that the horizontal positioning accuracy of Google Earth is better than 3 m [38][39][40]. Given that the resolution of GF-1 WFV is 16 m, the accuracy of Google Earth renders it appropriate for validation and to illustrate the influence of compensation.…”
Section: Accuracy Validationmentioning
confidence: 99%
“…Annual land cover can be recorded using historical VHR images such as Quickbird in GE [14], although lower volumes of VHR images were found in unpopulated areas and remote areas as well as sufficient historical VHR data were not available in GE for some years (e.g., data were relatively sparse in 2001, 2002, 2007, and 2008). Several recent studies have reported the geo-referencing errors of VHR images in GE to be in the range of 1.8-5.0 m RMSE [70][71][72]. While the geo-referencing accuracy should be taken into account for all VHR images, this is impractical and any errors would not affect our results severely because the coarse (231.7 m) resolution data was used.…”
Section: Reference Datamentioning
confidence: 99%